Women’s experiences with and preferences for contraceptive side effect counseling and management: A qualitative study from Ethiopia and Kenya - Lauren Suchman; Beth Phillips; Serah Gitome; Hailemichael Bizuneh; Hanna Feleke; Zachary Kwena; Sarah Okumu; Pauline Wekesa; Elizabeth A. Bukusi; Kristen Kirksey; Kelsey Holt; Jenny Liu; et al. (PLoS ONE, 2026)
Objective The magnitude of contraceptive non-use attributed to side effects globally merits concerted attention to ensure women receive quality side effect counseling and support in line with their goals. Evidence shows comprehensive contraceptive counseling can help women navigate side effects, yet survey data reveal consistent gaps in side effect counseling quality. To elucidate women’s lived experiences with side effect counseling and management, we examined how women in Kenya and Ethiopia manage contraceptive side effects with and without help from healthcare providers, and what their preferences are for support. Methods We conducted in-depth interviews with sexually active women of childbearing age (N = 83) in Nairobi and Kisumu, Kenya, and Addis Ababa and Amhara region, Ethiopia. Participants were asked about their contraceptive experiences, including side effects, how they managed side effects, what support they received, and their preferred approaches for receiving support when experiencing side effects. We utilized a modified grounded theory approach for data collection and analysis. Results We found gaps in reported counseling quality among women in our sample, and a desire for more comprehensive counseling on side effects during initial and follow-up visits. After experiencing side effects, most participants described enduring and self-managing with over-the-counter remedies, and seeking clinical advice only when they worried about how their contraceptive method was affecting their overall health. Follow-up services often addressed participants’ immediate needs, but rarely offered additional information or comprehensive counseling. A few participants were denied a desired contraceptive device removal or shamed for not using contraception. Conclusion We identified a need to improve anticipatory contraceptive side effects counseling and proactive follow-up approaches that support women to choose methods they prefer and then navigate their use or switching. Such counseling would help health systems become more responsive to patient needs in contexts where women’s suffering is often considered acceptable, rather than cause for intervention.